Neutrophils, NETs and multiple sclerosis: a mini review - Quan, Moyuan; Zhang, Huining; Deng, Xiaohong; Liu, Huijia; Xu, Yanqiu; Song, Xiujuan (Frontiers in Immunology, 2025)
Multiple sclerosis (MS), a chronic inflammatory and degenerative autoimmune disease characterized by the activation of various inflammatory cells, leads to demyelination and neuronal injury. Neutrophils, often underestimated in MS, are gaining increased attention for their significant functions in MS patients and the experimental autoimmune encephalomyelitis (EAE) animal model. Neutrophils play multiple roles in mediating the pathogenesis of autoimmune diseases, and numerous studies suggest that neutrophils might have a crucial role through neutrophil extracellular trap (NET) formation. Studies on NETs in MS are still in their infancy. In this review, we discuss the clinical perspective on the linkage between neutrophils and MS or EAE, as well as the role of NETs in the pathogenesis of MS/EAE. Further, we analyze the potential mechanisms by which NETs contribute to MS, the protective effects of NETs in MS, and their value as targets for disease intervention. NET formation and/or clearance as a therapeutic approach for MS still requires research in greater depth.